MENGGAGAS KONSEP ENTREPRENEURSHIP BERWAWASAN MULTIDIMENSI: MENGGAGAS KONSEP ENTREPRENEURSHIP BERWAWASAN MULTIDIMENSI - Ida Bagus Radendra Suastama (Forum Manajemen, 2009)
Negative perception about business people as the profit pursuer is, at one side, normal, but at the other side, becoming a concern of business people themselves to prevent such perception increases as stigma that business people think that â€œthe end justify the meansâ€, or in other words, in order to gain the profit, the business people could take any means deemed necessaary regardless the ethics and/or moral considerations. In order to avoid such negative perception, this paper offers a concept named multidimensional entrepreneurship. It is expected that such concept, if implemented thoroughly, not only minimise negative views, but also provide plenty of plus values toward business world, and eventually, many useful things for the societies and human beings. The aspects or dimensions offered to be considered are consisiting of : socio-cultural aspect, politic-economy (ideological) aspect, East-management aspect, science & technology aspect, business-law aspect, and spiritual aspect. The explanation of each aspect or dimension, including the values and the views brought by each of them will be further elaborated in following paper.